Penyelesaian Tindak Pidana yang Dilakukan Anak Melalui Diversi Dalam Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak - Akhmad Munawar; Sudiyono Sudiyono; Muhammad Deny Sugiyanto (Al-Adl : Jurnal Hukum, 2023)
In the Indonesian constitution, children have a strategic role: "The state guarantees the right of every child to survival, growth, and development as well as protection from violence and discrimination". Children are an integral part of human survival and the survival of a nation and state. Therefore, children's best interests should be internalized as the best interests for the survival of mankind. The consequences of the provisions of Article 28B of the 1945 Constitution of the Republic of Indonesia need to be followed up by making government policies aimed at protecting children. To protect the interests of children, the state established Law Number 23 of 2002 concerning Child Protection, amended by Law Number 35 of 2014 concerning Child Protection. More specifically the state also regulates the protection of children who commit crimes. in Law Number 3 of 1997 concerning Juvenile Court which was replaced by Law Number 11 of 2012 concerning the Child Criminal Justice System; however, even though the law has been formed, especially in the settlement of criminal acts committed by children through diversion, there are still weaknesses and legal vacuum. The first formulation of the problem in this study is What are the requirements for a crime that can be diversified in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System? and the second formulation of the problem is What are the juridical consequences if diversion is not carried out by law enforcers in Law Number 11 of 2012 concerning the Child Criminal Justice System? To analyze these problems, the researcher used normative research by reviewing and analyzing laws and regulations related to the settlement of crimes committed by children through diversion in Law Number 11 of 2012 concerning the Child Criminal Justice System.